2013
DOI: 10.1247/csf.12024
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Recognition of Cells with Elevated Calcium Is Mediated by Carbohydrate Chains of CD43

Abstract: ABSTRACT. Macrophages remove deteriorating cells (those undergoing apoptosis and oxidation) via poly-Nacetyllactosaminyl chains on CD43 caps, a major cell-surface glycoprotein. Unusually high intracellular calcium levels are also deteriorating for cells and tissue. Here we artificially elevated calcium levels in cells and examined the mechanism by which this elevation was resolved by macrophages. Results showed that treatment with the calcium ionophore A23187 and ionomycin induces capping of CD43 on Jurkat cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23]35) This study showed that Aβ42 is also a ligand for nucleolin. These observations support the idea that nucleolin on the surface of phagocytes has a general scavenger-like ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20][21][22][23]35) This study showed that Aβ42 is also a ligand for nucleolin. These observations support the idea that nucleolin on the surface of phagocytes has a general scavenger-like ability.…”
Section: Discussionmentioning
confidence: 99%
“…12,13) Previous studies have shown that macrophages utilize nucleolin to recognize and phagocytose apoptotic and oxidized cells 14,15) as well as living cells that have been treated with cytochalasin B and A23187. 16,17) Nucleolin-mediated recognition is therefore simple and powerful, as indicated by the indiscriminant removal of cells. Nucleolin is also a receptor for lipoproteins, 18) coxsackie B virus, 19) human immunodeficiency virus, 20) human parainfluenza virus type 3, 21) and enterohemorrhagic Escherichia coli O157 : H7.…”
mentioning
confidence: 99%
“…Unusual high intracellular calcium levels, observed in pathological conditions such as systemic lupus erythematosus (SLE), Alzheimer's disease, and brain trauma, result in capping of CD43. Similar to what happens with apoptotic cells, capped CD43 interacts with the macrophage receptor nucleolin, leading to recognition and phagocytosis of viable cells with elevated intracellular calcium levels by macrophages (Miki et al 2013).…”
Section: Cd43 and Noninfectious Diseases: A Poorly Understood Functionmentioning
confidence: 91%
“…The immune effectiveness can be improved with elevation of extracellular Ca concentrations in the range of physiologic levels of Ca signaling [ 46 , 47 ]. In vitro studies with macrophage-like cell lines U937 and MH-S [ 48 ] demonstrated that macrophage recognition to elevated Ca involves a sensor zone on the carbohydrate chains of CD43 [ 49 ].…”
Section: Macrophage Functions In Calcium-dependent Mannermentioning
confidence: 99%